Medication Adherence in Diabetes Mellitus Patients - Aladin, Aladin; Gustina, Erna; Zaman, Chairil (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Adherence to medication is a crucial factor in the management of diabetes mellitus (DM), a chronic metabolic disease that can lead to serious complications if not properly managed. This study aims to analyze the level of medication adherence among DM patients at Puskesmas Peninggalan, Musi Banyuasin Regency, in 2024. The research uses an observational design with a cross-sectional approach, involving 1,182 DM patients receiving treatment at the health center. Data were collected through structured interviews and medical record analysis, followed by descriptive and inferential analysis. The results show that patient adherence is influenced by factors such as age, education level, family support, and access to medication. These findings are expected to serve as a reference for improving more effective DM management strategies in primary healthcare facilities, with p-values of 0.002 for relationships, 0.004 for education, 0.001 for knowledge, 0.004 for attitudes, 0.003 for motivation, 0.006 for family support, and 0.001 for the role of healthcare staff. Conversely, a p-value of 1.000 showed no relationship between gender and medication adherence for diabetes mellitus. Proper management of diabetes mellitus patients, particularly in improving medication adherence, is crucial to prevent further complications. Therefore, it is recommended that the Health Department develop regular health education policies through various channels, including direct meetings and other media.